2017
DOI: 10.1002/macp.201600555
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Functional Grafted Electrospun Polymer Microfiber Scaffold Hosted Palladium Nanoparticles for Catalyzing Redox Reactions

Abstract: Porous poly(ether sulfone) (PES) microfiber mat has been prepared by electrospinning technique using the optimized conditions. The reducing moiety has been attached covalently to the PES microfiber mat by UV‐graft polymerization of glycidylmethacrylate, and reacting subsequently with hydrazine via epoxy ring opening. The grafted polymer shell around porous microfiber has been found to perform the reduction of precursor ions by grafted hydrazine which leads to the nucleation and growth of Pd nanoparticles (NPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Another interesting recent work is that from Pandey's team [140], who used electrospinning to prepare poly(ether sulfone) (PES) fibers and took advantage of the presence of the ether sulfone moieties to perform photolysis under UV irradiation to initiate the growth of polyGMA chains. The pendant oxirane groups were then opened with hydrazine providing directly attachment of the reducing agents on the support surface.…”
Section: Nanoparticles Supported By Biporous Polymersmentioning
confidence: 99%
“…Another interesting recent work is that from Pandey's team [140], who used electrospinning to prepare poly(ether sulfone) (PES) fibers and took advantage of the presence of the ether sulfone moieties to perform photolysis under UV irradiation to initiate the growth of polyGMA chains. The pendant oxirane groups were then opened with hydrazine providing directly attachment of the reducing agents on the support surface.…”
Section: Nanoparticles Supported By Biporous Polymersmentioning
confidence: 99%
“…It is interesting to note that the toxicities of the heavy metal ions are highly dependent upon their chemical forms. For example, Cr(VI) ions can be converted to lesser toxic and labile Cr(III) form by the catalytic reduction …”
Section: Introductionmentioning
confidence: 99%
“…For example, Cr(VI) ions can be converted to lesser toxic and labile Cr(III) form by the catalytic reduction. [8][9][10] In recent years, several attempts have been made to prepare low-cost and most effective adsorbents for the removal of toxic metal ions. Some of these adsorbents are fly ash, [11] fertilizer industrial waste, [12] titanium oxide, [13] red mud, [14] clay montmorillonite, [15][16] sawdust, [17] biomass materials, [18][19] yeast and microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the neutral weak basic (no ion-exchange sites) membrane not only provides the optimum interactions with the nanocatalyst but also holds high amount of the metal NPs. 7,19 Among the noble metals, palladium (Pd) has been studied extensively as the prime catalyst for the applications in industrial and biological important coupling reactions involving carbon−carbon and carbon-heteroatom coupling reactions, 20−22 remediation of toxic ions including nitrite reduction, 23 synthesis of nanoreactors, 24 reduction of Cr 2 O 7 2− /CrO 4 2− anions to Cr 3+ ions, 25,26 and reduction of UO 2 2+ to U 4+ ions 5,6 having applications in nuclear industries. Palladium and Pd NPs supported on solid matrices (heterogeneous) have been extensively used in many organic coupling reactions 18,27 and inorganic transformations which found to exhibit better catalytic activity compare to their traditional homogeneous analogues such as Pd(OAc) 2 and PdCl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, this physical instability could be avoided by using appropriate surfactants during NPs syntheses. However, these NPs suspended in colloidal solutions are difficult to handle/withdraw, and also surfactant coatings on NPs may block the catalytic sites, which would slower the reaction kinetics by hindering the interaction of reactants with the catalyst surface. These problems can be addressed by immobilizing the NPs on insoluble solid supports such as synthetic polymer membrane as given in our earlier publications, silica (SiO 2 ), alumina (Al 2 O 3 ), carbon nanomaterials (carbon nanotubes, graphene oxide), TiO 2 film, superparamagnetic materials (Fe 3 O 4 ), etc. Among the solid supports, the porous polymeric membrane provides not only better physical and chemical stability but also high accessibility of the NPs to reactants. It is also possible to tune the size and shape of the NPs, and have added advantage of ease of handling/withdrawing for recycling.…”
Section: Introductionmentioning
confidence: 99%